Magnetic resonance imaging parameters for assessing risk of recurrent hamstring injuries in elite athletes - Koulouris, G.; Connell, D. A.; Brukner, P.; Schneider-Kolsky, M. (The American Journal of Sports Medicine, 2007)
Background: Magnetic resonance (MR) imaging has established its usefulness in diagnosing hamstring muscle strain and identifying features correlating with the duration of rehabilitation in athletes; however, data are currently lacking that may predict which imaging parameters may be predictive of a repeat strain.